ANALISIS KESALAHAN SISWA BERDASARKAN PROSEDUR NEWMAN DALAM MENYELESAIKAN SOAL CERITA MATERI PECAHAN PADA KELAS IV SD NEGERI MANYARAN 02 SEMARANG - Tia Pramesti; Sukamto Sukamto; M. Yusuf Setia Wardana (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
The aims of the research are to determine the types of errors made by students in solving fraction material story questions and to determine the causes of student errors in solving fraction material story questions based on the Newman procedure. Research subjects were 6 subjects with 2 upper groups, 2 moderate groups, and 2 low groups. The techniques of data collection used interviews, written tests, and documentation. The results showed that the research subjects experienced errors on each item with various types of errors, namely reading errors that did not occur at all with a percentage of 0%, errors in understanding the problem were 9 times with a percentage of 30%, error transformation problems were 7 times with a percentage of 23.34%, errors in processing skills were 10 times with a percentage of 36.66%, and errors in writing the final answer were 4 times with a percentage of 2.64%. Furthermore, there are several causes in errors namely confusion about how to solve the questions, misunderstanding the meaning of the questions, misunderstanding the concept of fractions and not being careful in solving problems.